21 Genetics and Genomic Approaches for Sustainable Dairy Cattle Improvement in Smallholder Dairy Systems. (21st September 2022) - Mrode, Raphael; Ekine-Dzivenu, Chinyere; Ojango, Julie; Okeyo, Mwai
Abstract: This study examines genetic and genomic approaches for sustainability in the dairy systems of developing countries of sub-Saharan Africa, where farms are predominately managed by smallholders, with 80% of land holdings being smaller than ten hectares. Sustainability in these systems involves addressing the global challenges of climate change while ensuring food security. Feed intake is a major trait with huge impact on both the efficiency of small holder systems and on methane emission. Improvement in feed efficiency will both mitigate the effects of climate change and reduce the cost of milk production. Body weight provides an indirect means of improving feed efficiency for body maintenance. Using daily milk yield and body weight records for 2716 cows, genomic predictions were undertaken, and a selection index for improving milk yield while restricting changes in body weight was implemented in Tanzania. However, defining broader breeding goals continue to be a challenge due to the lack of data but collection of milk components and somatic cell counts is being piloted in Tanzania and Ethiopia. Breeding for heat tolerance has been based on the rate of decline in milk yield due to changes in the temperature and humidity index (THI). An analysis of 14, 367 daily milk records of 3511 dairy cows and weather records in Tanzania indicated that heat stress significantly affected daily milk production and reduced milk yield by 4.16% to 14.42% across THI groups. Reaction norms for sire EBVs along the trajectory of THI indicates that genetic variations exist which can be used to select animals that perform optimally in different environments. Also, other indicators of resilience including log-transformed variance and skewness of deviation, based on fluctuations in animals' milk yield have been examined. Cows with less than 50% of exotic dairy genes showed significant levels higher degree of resilience.